Study of protective Effect of Gamma Rays of Alcoholic Extract of Myrtus Communis L. Leaves Using Micronucleus Assay in Human Lymphocytes - إبراهيم, نهلة; اختيار , عدنان; الجهماني, علا (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to investigate the protective effect of the alcoholic extract of leaves of the Myrtus communisL plant from the genetic toxicity caused by gamma rays in human lymphocytes in five healthy adult donors. Irradiation was done at a dose of 2 Gy and the extract was added to cell cultures at two different concentrations 50 and 100 µg/ml immediately after irradiation of the samples. The results showed that the extract caused a decrease in the frequency of micronuclei induced by gamma rays at concentrations 50 and 100 µg/ml (P˂0.05) compared to the irradiated group, It was observed that the concentration 100 µg/ml of the extract caused a greater decrease in the frequency of the micronuclei compared to the concentration of 50 µg/ml and no significant differences were observed in the frequency of the micronuclei between the two groups (P<0.05).